Assessing the Implementation of Complete Systematic Land Registration (PTSL) Based on Good Governance Principles in Ensuring Legal Certainty of Land Rights in Indonesia - Nurdin; Mukmin Muhammad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to assess the implementation of the Complete Systematic Land Registration (PTSL) program based on good governance principles in ensuring legal certainty of land rights in Indonesia. The research employs a qualitative method with a socio-legal approach, focusing on the empirical context of PTSL implementation in Barru Regency. Data were collected through in-depth interviews with officials of the National Land Agency (BPN), community participants, field observations, and document analysis. The collected data were systematically analyzed using NVivo 12 Pro to identify key themes related to governance practices, legal certainty, institutional roles, and implementation challenges.The findings indicate that the implementation of PTSL has generally adhered to structured administrative and technical procedures, including document verification, land measurement, and digital registration systems. The application of good governance principles is reflected in transparency through public outreach, accountability in procedural compliance, and participation involving local governments and communities. However, the study also identifies several persistent challenges, such as inaccuracies in legacy land certificates, overlapping land claims, and limitations in public administrative readiness, which may hinder the effectiveness of the program.Furthermore, the PTSL program has significantly contributed to strengthening legal certainty by formalizing land ownership, reducing the potential for disputes, and enhancing the socio-economic value of land. Legal certification provides stronger protection of property rights and facilitates access to economic resources, including financial services. Nevertheless, the sustainability and success of the program depend on accurate data submission, continuous institutional supervision, and strengthened coordination among stakeholders.In conclusion, the implementation of PTSL based on good governance principles plays a vital role in ensuring legal certainty of land rights in Indonesia. This study recommends improving data validation mechanisms, enhancing community awareness, and reinforcing institutional collaboration to optimize the effectiveness and long-term impact of the program